1983
DOI: 10.1007/bf00020157
|View full text |Cite
|
Sign up to set email alerts
|

A fracture mechanics study of the fatigue of rubber in compression

Abstract: Repeated deformation of rubber cylinders in compression causes cracks to initiate at tensile stress concentrations (eg. bond edges). The cracks grow to remove the rubber which at maximum deformation bulges outside the original profile of the cylinder. The results are analysed in terms of fracture mechanics. The tearing energy, T is substantially independent of crack length. The relation between crack growth rate d c/d N and T appears to be a material property, independent of testpiece geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Stevenson [4] conducted a study of fatigue crack growth of rubber in compression with a cylindrical specimen. He concluded that crack growth in compression occurs at an approximately constant rate and is restricted to the outer regions of the test specimen with high local shear strains.…”
Section: Introductionmentioning
confidence: 99%
“…Stevenson [4] conducted a study of fatigue crack growth of rubber in compression with a cylindrical specimen. He concluded that crack growth in compression occurs at an approximately constant rate and is restricted to the outer regions of the test specimen with high local shear strains.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Stevenson (22) studied the formation of cracks in bonded rubber blocks. He found cracks to initiate at the bonded surfaces under tensile stress concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Stevenson and Thomas25 observed the bursting of a natural rubber balloon. Another study of Stevenson26 was about fracture mechanics study of the rubber fatigue in compression. He found that fatigue crack growth occurred in compression at an approximately constant rate, and tearing energy was restricted to the outer regions of the test pieces with high local shear strains.…”
Section: Introductionmentioning
confidence: 99%